MANAJEMEN KOMPENSASI DALAM MENINGKATKAN KINERJA DOSEN DI PERGURUAN TINGGI BERBASIS PONDOK PESANTREN (STUDI PADA SEKOLAH TINGGI ILMU TARBIYAH SIBAWAIHI MUTAWALLI JEROWARU) - Ihtiar Akbar, Hasan; Hapipi, Hapipi (CV. Lafadz Jaya, 2024)
Compensation is a fundamental factor in improving the performance of a teacher or lecturer. In order to create good management, universities must be able to manage well and fairly. Good management will create good human resources, and vice versa. If management is not good, human resources will not function properly. This research aims to find out how monetary funding improves the performance of lecturers at Islamic boarding school-based universities (Studies at the Sibawaihi Mutawalli Jerowaru College of Science). The method used in this research is descriptive qualitative. The research results in this study are that funding was funded directly by the foundation management on the recommendation of the chairman of the Sibawaihi Mutawalli Jerowaru Tarbiyah College of Science which was seen based on the lecturers' working hours or workload. Compensation management at the Sibawaihi Mutawalli Jerowaru Islamic Tarbiyah College. Includes planning, organizing, implementing and monitoring.